Epidemiology of childhood enterovirus infections in Hangzhou, China - Li, Wei; Zhang, Xiao; Chen, Xi; Cheng, Yu-Ping; Wu, Yi-Dong; Shu, Qiang; Chen, Xue-Jun; Shang, Shi-Qiang (Virology journal, 2015)
BACKGROUND: There are over 100 serotypes of enterovirus species A-D, which are the common cause of various symptoms in infants, such as meningitis, encephalitis and hand foot mouth disease (HFMD). This study aims to investigate the epidemiological characteristics of enteroviruses in Hangzhou, Zhejiang province, China, and to provide relevant information to guide public health responses and interventions. METHODS: Systematic surveillance was conducted on enterovirus infections. Samples were collected from children admitted to the inpatient wards and outpatient departments between January 2010 and December 2012 in the Children’s Hospital, Zhejiang University School of Medicine. Enteroviruses from all specimens were detected by RT-PCR using a commercialized detection kit. RESULTS: From 13026 samples collected and examined, 2673 (21.21%) were found positive for enteroviruses. The annual enterovirus-positive rate decreased from 32.78% in 2010 to 14.23% in 2012. Positivity rate for enteroviruses was highest among children aged less than 5 years. The monthly positivity rate for enterovirus infection ranged from 2.6% to 34.83%, with a peak in June and July. Serotypes causing severe symptoms such as HFMD including EV71 and CA16 were decreasing, while the proportion of unidentified EV serotypes causing herpangina and viral encephalitis were on the rise. CONCLUSIONS: EV infection is highly prevalent among young children in Hangzhou, as it is in the most other parts of the world. Further surveillance using methods that can subtype all EVs is warranted to better monitor these infections and their etiology.